New Potentialities for Utilization of Associated Petroleum Gases in Power Generation and Chemicals Production - V. S. Arutyunov; V. I. Savchenko; I. V. Sedov; A. V. Nikitin; K. Yu. Troshin; A. A. Borisov; I. G. Fokin; I. A. Makaryan; L. N. Strekova (Eurasian Chemico-Technological Journal, 2017)
New possibilities for the utilization of associated petroleum gases (APG) and monetization of small-scale and remote Natural Gas resources by power generation and chemicals production are considered and tested. One possibility is the oxy-cracking of APG. This technology allows selective transformation of heavier hydrocarbons that have low octane (methane) numbers and inclined to soot and tar formation, into lighter compounds with higher octane numbers, thus producing gas suitable to feed different types of power engines. Another possibility is the small-scale conversion of APG to syngas to produce more easily transportable and more valuable chemicals or liquid fuels via well-known Fischer–Tropsch process or catalytic synthesis of methanol. For this purpose we have suggested principally new technology for natural gases conversion into syngas, based on the use of 3D (volumetric) matrixes. It allows the relative simple and very compact non-catalytic reformers to be designed for small-scale gas-to liquid (GTL) technologies. Their main advantages are autothermal character of the process without any need in additional heating or power supply, absence of catalyst that allows processing hydrocarbon gases of practically any composition, including APG, without additional pretreatment, very high specific volume capacity, at any rate 10 times higher than that of steam reforming, and simplicity in construction and operation.